Association of Calpain10 polymorphisms with polycystic ovarian syndrome susceptibility: a systematic review and meta-analysis with trial sequential analysis - Li, Yamei; Han, Ting; Wang, Yingxia; Gao, Jie; Zhang, Jianglin; Wu, Yinglan; Luo, Jiayou (Frontiers in Genetics, 2023)
Insulin resistance plays an important role in the pathogenesis of polycystic ovarian syndrome (PCOS). Calpain10 (CAPN10) gene was the first identified susceptibility gene for type 2 diabetes mellitus and closely related to insulin sensitivity. A lot of research attention has been attracted on the relationship between CAPN10 polymorphisms and PCOS risk, but they didn't reach a consistent conclusion. We therefore performed this systematic review and meta-analysis to assess the association of CAPN10 common variants with PCOS susceptibility.A total of 21 studies were eligible for inclusion. Meta-analyses were done for 5 variants that had at least two data sources: UCSNP-19, -43, -44, -56 and -63. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated under five genetic models. Subgroup analyses by ethnicity, PCOS diagnostic criteria, and source of controls were conducted. Moreover, false-positive report probability (FPRP) test and trial sequential analysis (TSA) were performed to assess the significant associations. The results showed a possible negative association between UCSNP-19 and PCOS risk (ins/ins vs del/del + del/ins: OR=0.84, 95% CI: 0.72-0.98). In subgroup analyses, FPRP test indicated that noteworthy associations were observed in mixed ethnicities for UCSNP-43 (A vs G: OR=1.81, 95% CI: 1.17-2.79; AA + AG vs GG: OR=2.14, 95% CI: 1.20-3.80) and in Asians for UCSNP-44 (CC vs TT: OR=2.07, 95% CI: 1.21-3.51; CC vs CT + TT: OR=2.19, 95% CI: 1.31-3.69), but TSA plots showed that the accumulated sample sizes of these associations were insufficient to draw firm conclusions. In summary, our study suggested that UCSNP-19, UCSNP-43, and UCSNP-44 in CAPN10 gene may be involved in PCOS susceptibility. These findings warrant further studies.